2012
DOI: 10.1155/2012/153159
|View full text |Cite
|
Sign up to set email alerts
|

CES as an Efficient Natural Catalyst for Synthesis of Schiff Bases under Solvent-Free Conditions: An Innovative Green Approach

Abstract: A mild and efficient method has been reported for the preparation of Schiff base ligands through the condensation reaction of various aromatic aldehydes with substituted aromatic amines in the presence of CES (calcined eggshell) as a heterogeneous catalyst under solvent-free conditions. The advantages of this ecofriendly, economic method are simplicity of the reaction procedure, moderate to good product yields, and very short reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…ES powder was used as a catalyst for the synthesis of Schiff bases under solvent free conditions. 18 These will bond coordinately with metals to form metal complexes and are used as models for biological systems. 19 Numerous research studies have explored the synthesis of Schiff bases, 20,21 but they faced constraints such as long reaction time, low yield, use of toxic solvents and tedious workup procedures.…”
Section: Egg Shell Powder As a Catalyst For Organic Transformationsmentioning
confidence: 99%
“…ES powder was used as a catalyst for the synthesis of Schiff bases under solvent free conditions. 18 These will bond coordinately with metals to form metal complexes and are used as models for biological systems. 19 Numerous research studies have explored the synthesis of Schiff bases, 20,21 but they faced constraints such as long reaction time, low yield, use of toxic solvents and tedious workup procedures.…”
Section: Egg Shell Powder As a Catalyst For Organic Transformationsmentioning
confidence: 99%
“…191 The reaction involves the formation of an alkoxide complex in the first step by adsorption of an alcohol 252,253 However, the reaction between carbonyl species and amines is considered noncatalytic during reaction which needs to be further confirmed as similar reactions are proposed to occur over nonmetallic catalysts. 254,255 Abbenhuis et al reported the effect of the base in the Ru-catalyzed amination reaction cycle Figure 14B. 188 It is proposed that the base enhances the formation of Ru-alkoxy species by an efficient abstraction of hydrogen leading to a protonated base.…”
Section: Amination Of Biomass-derived Oxygenatesmentioning
confidence: 99%
“…The importance of carbazides, carbazones, thiosemicarbazide, and their transition metal complexes has grown in a short period of time because of the discovery of their effects on flu, protozoa, variola (smallpox), certain types of tumors, and fungi [13][14] and their corresponding derivatives thiosemicarbazide are related to several essential antimicrobial activities 15 . Fungicidal, anthelmintic, anti-bacterial, activity 16 . Schiff bases derived from simple thiosemicarbazide and its derivatives are found to be very effective in the field of pharmacology and other imp medicinal fields 17 .…”
Section: Introductionmentioning
confidence: 99%